2022
DOI: 10.1002/wsbm.1576
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of immune effector cell‐associated neurotoxicity syndrome after CAR‐T treatment

Abstract: Chimeric antigen receptor T-cell (CAR-T) treatment has revolutionized the landscape of cancer therapy with significant efficacy on hematologic malignancy, especially in relapsed and refractory B cell malignancies. However, unexpected serious toxicities such as cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS) still hamper its broad application. Clinical trials using CAR-T cells targeting specific antigens on tumor cell surface have provided valuable information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 184 publications
0
18
0
Order By: Relevance
“…The mechanism of CAR T-cell neurotoxicity remains to be well-elucidated, and several mechanisms of ICANS after CAR T-cell treatment have been described ( 29 ). The most widely accepted mechanism of CAR T-cell neurotoxicity is driven by systemic inflammation and cytokine production.…”
Section: Car T-cell-associated Neurotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of CAR T-cell neurotoxicity remains to be well-elucidated, and several mechanisms of ICANS after CAR T-cell treatment have been described ( 29 ). The most widely accepted mechanism of CAR T-cell neurotoxicity is driven by systemic inflammation and cytokine production.…”
Section: Car T-cell-associated Neurotoxicitymentioning
confidence: 99%
“…This triggers a further local inflammatory response and CNS inflammation with subsequent astrocyte injury and microglial activation. It then results in abnormal neuronal function related to the dysregulation of neuroglial cells and neurotransmitters ( 29 ). In addition, cerebral multifocal hemorrhage in patients with ICANS indicates thrombotic microangiopathy compromising BBB function ( 29 ).…”
Section: Car T-cell-associated Neurotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The entry of peripheral immune cells and cytokines into the CNS can lead to CNS inflammation. Activated astrocytes release IL‐6 and GM‐CSF, which induces microglial activation to produce additional IL‐1β, IL‐6, and TNF‐α, further impairing neuronal function 108 . Clinical observations have shown that higher tumor burden, prior lymphocyte depletion, larger CAR‐T cell infusion doses, and more rapid CAR‐T cell expansion in vivo are also associated with the occurrence and severity of ICANS 108,109 .…”
Section: Tme and Clinical Response Of Car‐t Cell Therapymentioning
confidence: 99%
“…Activated astrocytes release IL‐6 and GM‐CSF, which induces microglial activation to produce additional IL‐1β, IL‐6, and TNF‐α, further impairing neuronal function 108 . Clinical observations have shown that higher tumor burden, prior lymphocyte depletion, larger CAR‐T cell infusion doses, and more rapid CAR‐T cell expansion in vivo are also associated with the occurrence and severity of ICANS 108,109 . The destruction of blood–brain barrier (BBB) also leads to the migration of T cells (including CAR‐T cells) to the brain parenchyma, and the levels of cytokines and proteins would be increased in the cerebrospinal fluid, then leading to CNS inflammation and toxicity.…”
Section: Tme and Clinical Response Of Car‐t Cell Therapymentioning
confidence: 99%